THOUGHT PRESENTATION IN KATHRINE MANSFIELD'S SHORT STORIES - ھدى ھادي خلیل (College of Education for Women, 2019)
To cite the short stories of Kathrine Mansfield, all contain characters who are revealed through their own thoughts. In her stories, the world is always seen through the eyes of her characters in the form of points of view presented to the readers through the characters' minds. This way of revealing characters and figuring out the world, through the presentation of the characters' thoughts, is linked to the 'stream of consciousness.' Kathrine Mansfield has been compared with Virginia Woolf in particular in that both writers used the thoughts and the points of view of their characters as material for their work through the stream of consciousness. According to Leech and Short (1981), there are five linguistic techniques available for the narrator to present his/ her characters' thoughts through. These are the direct thought, the free direct thought, indirect thought, free indirect thought and narrative report of thought act. The narrator is free to use any, some or all of these techniques to inform the reader of what is going in the characters' minds to make him/ her aware of certain points of view. The present paper attempts to present full exposition of the five techniques of thought presentation mentioned above. This exposition is presented in the first section of the paper. The paper mainly aims at making a stylistic analysis of thought presentation by the five techniques in Mansfield's short stories. The analysis is done by investigating and examining the corpus which consists of thirteen short stories chosen randomly. The results of the analysis are presented through certain conclusions supported by statistics and examples which are quoted extracts chosen from the stories analysed. Almost each extract is accompanied by brief explanation of part of the plot which the extract is concerned with. The brief explanation helps the reader to comprehend both the extract and the conclusion arrived at. The paper is of a linguistic value and a literary value. The linguistic value lies in the full exposition of the five techniques of thought presentation and their application on the literary corpus. A linguist can follow the same steps and apply the five techniques on other literary works, whether short stories or novels. The literary value lies in the analysis of the presentation of thought in a literary work (Mansfield's short stories) since there is a close link between the presentation of thought and the stream of consciousness which is a common technique of writing in many narrative works.